Which Boats are lifted by a Foreign Tide? Direct and Indirect Wage Effects of Foreign Ownership - Sourafel Girma; Holger Görg; Erasmus Kersting (Journal of International Business Studies, 2019)
The attraction of foreign direct investment (FDI) is considered to be of particular importance for emerging economies because it represents a channel through which international convergence in standards of living may be achieved. One important effect of FDI is its impact on wages, both within the targeted firm (direct) and the local firms within the same geographic region and sector (indirect). In this paper we investigate the question whether multinational enterprises (MNEs) raise or lower wages directly and indirectly, both theoretically and empirically. Importantly, the magnitude of these changes may depend on how many firms in the sector are already foreign-owned. Generally, the effect of MNEs on wages has not been studied as intensively in the international business (IB) literature as other aspects of FDI, and ours is the first article to specifically investigate the moderating effect of variation in foreign employment shares across industry-province cells (clusters). Using Chinese data on 146,199 firms we estimate the direct wage effect of foreign ownership to be positive and to increase with the employment share of foreign owned firms. We also find that the indirect effect on domestic wages varies with the foreign share and may even turn negative.
Keywords: F12; F16; F23; F61; 330; Foreign Direct Investment; Wage effects; Spillovers